PENGEMBANGAN POP UP BOOK COPING SELF-TALK UNTUK MENGENGENDALIKAN AGRESIVITAS SISWA SEKOLAH DASAR DI SDN 197/IX PEMATANG GAJAH - Rizki Islami Pasa; Nelyahardi Gutji; Muhammad Zulfikar (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
This research aims to describe the process of developing pop up book media to deal with students who behave aggressively. The research method used in this research is research and development (R&D) with the Borg and Gall development stages which have been simplified by Sutja, namely there are five stages including preliminary study, product development, product validation and revision, limited trials and product revision. TheresearchwasconductedatSDN197/IXPematangGajahwith the subject of aggressive behavior that occurred in grade 4 students. The data collection technique used was validation sheets from material experts, media experts and practitioners. The data analysis technique used in this research is qualitative descriptive analysis and quantitative descriptive analysis.